Indications on self mode-locking in a broad area single-section quantum dot laser. (December 2019) - Auth, D; Korenev, V V; Savelyev, A V; Maximov, M V; Zhukov, A E; Breuer, S
Abstract: Broad-area edge-emitting monolithic mode-locked semiconductor quantum dot lasers emitting at 1.26 μm could potentially serve as ideal sources for the generation of high power broad optical frequency combs for short-reach inter and intra data-center links. In this contribution, the inter-mode beat frequency of a 2 mm long InAs/InGaAs quantum dot laser with a broad-ridge waveguide are studied experimentally. Laser output power, radio-frequency and spectral domain analysis is performed. -3 dB spectral widths ranging from 2nm to 5.3 nm and the existence of an inter-mode beat frequency at 20.4 GHz with a signal-to-noise ratio from 2 dB up to 11 dB are experimentally confirmed for injection currents from 0.225 A to 1 A. Our results indicate a potential way towards high output power optical frequency comb generation by electrically injected monolithic semiconductor lasers.